The Relevance of Career Interest among PGPAUD Students to Study Program Alignment and Career Realism - Andia Paqita Aprilian Putri; Edi Waluyo (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to examine the relationship between career interests of PGPAUD students with the relevance of the study program and the real situation in the workplace. This research is based on the misalignment between the study program taken and the career that will be chosen by some PGPAUD students, while the compatibility between the two is an important factor related to preparing superior and quality graduates in the field of early childhood education. This study uses quantitative methods with a descriptive correlational approach. The research sample was 36 PGPAUD students of Semarang State University Class of 2021, which was determined through a total sampling technique. Data collection was conducted using an online-based questionnaire with a Likert scale, which included three main variables, namely PGPAUD students' career interest (X1), career reality (X2), and study program suitability (Y). More than 50% of students gave positive responses regarding their interest in pursuing a career in PAUD. In addition, the results showed a strong relevance between variables.